Consider the polynomial identity (difference of squares):
(x+y)(x-y) = x² - y²
Set x =7 and y = 2 to obtain
(7+2)*(7-2) = 7² - 2²
9*5 = 49 - 4
45 = 49 - 4
This is the result required, obtained by using difference of squares.
Answer: Difference of squares.
Question
Which of the following equations is equivalent to 5(2p-6)=40?
Let's solve your equation step-by-step.
5(2p−6)=40
Step 1: Simplify both sides of the equation.
5(2p−6)=40
(5)(2p)+(5)(−6)=40(Distribute)
10p+−30=40
10p−30=40
Step 2: Add 30 to both sides.
10p−30+30=40+30
10p=70
Step 3: Divide both sides by 10.
10p/10=70/10
p=7
ANSWER =
The answer is A. because...
10p−30=40 = p=7
ANSWER = A.
hope i helped have a wonderful day..can i get a brainliest please and thank you...
Answer:
16.15
Step-by-step explanation:
hope this helps
Answer:
p = -5
every element in the sequence is created by subtracting 3 from the pervious element.
Step-by-step explanation:
I am not sure you put every necessary information here.
but I'd the visible information is truly everything, then it's is trivial.
the difference between 4 and 1 is ... well, -3. meaning we subtract 3 from 4 to get 1.
we suspect this is the rule and keep trying.
1 -3 = -2
hey it works.
and -8 -3 = -11
hey, also correct.
and the difference between -2 and -8 is -6, and when we place another item in between (p), we cut that in half again to -3. so, it is all consistent.
therefore,
p = -2 -3 = -5
the rule is
an = an-1 - 3